Third generation P2Y12 antagonists inhibit platelet aggregation more effectively than clopidogrel in a myocardial infarction registry - Olivier, Christoph B.; Diehl, Philipp; Schnabel, Katharina; Weik, Patrick; Zhou, Qian; Bode, Christoph; Moser, Martin (Thrombosis and Haemostasis, 2014)
The current standard of antiplatelet therapy of patients after myocardial infarction includes the P2Y12 receptor antagonists clopidogrel, prasugrel or ticagrelor. This study aimed to compare the antiplatelet effect of clopidogrel, prasugrel and ticagrelor in patients after myocardial infarction. In a single-centre registry the antiplatelet effect of clopidogrel, prasugrel and ticagrelor was investigated by aggregometry in patients after myocardial infarction. To assess the overall capacity of platelet aggregation whole blood was induced with thrombin receptor activating peptide (TRAP; 32 μM). To specifically quantify the effect of P2Y12 antagonists, whole blood was stimulated with 6.4 μM adenosine diphophosphate (ADP). Relative ADP induced aggregation (r-ADP-agg) was defined as the ADP-TRAP ratio to reflect an individual degree of P2Y12-dependent platelet inhibition. Platelet function of 238 patients was analysed [clopidogrel (n=58), prasugrel (n=65), ticagrelor (n=115)]. The r-ADP-agg was 35 ± 14% for patients receiving clopidogrel, 28 ± 10% for patients receiving prasugrel and 26 ± 11% for patients receiving ticagrelor. The r-ADP-agg was significantly lower in patients treated with prasugrel (p=0.0024) or ticagrelor (p<0.0001) compared to clopidogrel. There was no significant difference between patients receiving prasugrel or ticagrelor (p=0.2559). In conclusion, prasugrel and ticagrelor provide a stronger platelet inhibition compared to clopidogrel in patients after myocardial infarction. No significant difference in platelet inhibition was detected between prasugrel and ticagrelor. (registry for patients after Myocardial Infarction Treated with AntiPlatelet agents; DRKS00003146).
Keywords: Clopidogrel; prasugrel; ticagrelor; platelet; aggregation; P2Y12